Biofunctional characteristics of dietary fiber extracted from Malaysian Ziziphus mauritiana L. leaves and its association in vitro antidiabetics properties - Zahari, Nur Syuhada (2021)
Ziziphus mauritiana L. derived from Rhamnaceae family plant (known as Bidara tree in Malaysia) has been consumed by Malaysian through processing the fruit into pickles or eating it fresh, while the leaves are frequently used in traditional medicine, particularly in Islamic medicine. Although the Z. mauritiana L. plant rich in macronutrients, micronutrients, and phytochemicals that offer health benefits, yet, it is still considered underutilized in Malaysia due to a lack of scientific information about the health promoting effect of its fiber. In other countries, Z. mauritiana L. also used widely as traditional medicine and recently researchers start to study scientifically the health benefits of this plant especially in Asian country. The purpose of the study was therefore to explore the physicochemical properties relevant to the nutritional quality of one of the sources of dietary fiber (mucilage) necessary for the maintenance of population health in the community, especially in treating diabetes mellitus. Additionally, the potent phenolic content and α-amylase and α-glucosidase enzyme inhibitory activity were also investigated. The extraction yield of mucilage was investigated from Z. mauritiana L. fruit pulp and leaves where the preliminary screening has shown that the higher mucilage yield was obtained from the leaves with 1.24%, while the mucilage from the pulp yielded 0.34%. The mucilage of Z. mauritiana L. leaves with good hydration properties of swelling capacity (6.87 ± 0.23 mL/g), water holding capacity (3.960 ± 0.200 g/g), oil holding capacity (0.507 ± 0.083 g/g), and its emulsifying properties including emulsifying activity (56.0 ± 4.00%) and emulsifying stability (70.87 ± 2.31%) indicate that it may have the capability in regulating postprandial hyperglycemia. Fourier transform infrared spectroscopy (FTIR) demonstrated the band of functional group characteristics of dietary fiber while scanning electron microscopy (SEM) analysis revealed the structural characteristic of the extracted Z. mauritiana L. mucilage. Glucose dialysis retardation index (GDRI) analysis on Z. mauritiana L. leaves dietary fiber showed decreasing effect overtime at minutes 60 (from 70.94 to 62.57%). The phytochemical analysis has shown that the total phenolic content of the fiber extract was 6.13 mg GAE/g dry sample extract while the total flavonoid content was 83.00 mg QE/g dry sample extract. In vitro studies exhibit excellent α- amylase and α-glucosidase inhibition activity with an IC50 of 138.3 μg/mL and 11.04 μg/mL, respectively as compared to one of synthetic drugs used for treating diabetes, acarbose. These features make the crude Z. mauritiana L. mucilaginous extract a remarkable candidate for functional food and nutraceutical dietary fiber especially in associated with antidiabetes